Determinants of Cost Recovery Rate of Inpatient Cases: Evidence from Indonesian Public Hospitals - Maqhfirah Rahayu; Heru Fahlevi; Ratna Mulyany (Jurnal Ilmiah Akuntansi, 2023)
This study aims examine the influence of patient profile, severity, length of stay, and bed class for cost recovery rate (CRR) of inpatient cases in three Indonesian public hospitals located in Aceh Province, Indonesia. Data were collected from hospital insurance claim from 2018 to 2020. The number of patient dataset collected in this study is 23,125 cases from top ten most frequent cases. Using Multiple Linear Regression, this study found that patient gender, age, length of stay, severity and bed class have a positive significant effect on CRR the inpatient cases. In addition, this study also used questionnaires to elaborate the perspective of managers and doctors in the public hospitals on cost management system and procedures in their hospitals. The results suggested that improved cost management system and procedures are required to improve CRR of the patient treatments.